2012
DOI: 10.1124/dmd.112.044545
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ring Oxidation of 4- or 5-Substituted 2H-Oxazole to Corresponding 2-Oxazolone Catalyzed by Cytosolic Aldehyde Oxidase

Abstract: ABSTRACT:The ring oxidation of 2H-oxazole, or C2-unsubstituted oxazole, to 2-oxazolone, a cyclic carbamate, was observed on various 4-or 5-substituted oxazoles. Using 5-(3-bromophenyl)oxazole as a model compound, its 2-oxazolone metabolite M1 was fully characterized by liquid chromatography/tandem mass spectrometry and nuclear magnetic resonance. The reaction mainly occurred in the liver cytosolic fraction without the requirement of cytochrome P450 enzymes and cofactor NADPH. Investigations into the mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In addition, they also contain one 4-aryl or 5-aryl substituted thiazole ring (in the AR ligand moiety ( 46 ) and the VHL ligand moiety ( 42 ), respectively). Although five-term moieties are commonly considered not prone to be metabolized by h AOX unless it is fused with a phenyl ring to give a benzothiazole, one exception has been reported by Arora et al, showing that 2H-oxazoles substituted at the C-4 or C-5 position with variably decorated phenyl rings can undergo oxidation by mouse cytosolic AOX to give the corresponding 2-oxazolones. Therefore, we hypothesized that a similar oxidation pattern could occur in the selected PROTACs although this reaction has not been reported for substituted thiazoles to date.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they also contain one 4-aryl or 5-aryl substituted thiazole ring (in the AR ligand moiety ( 46 ) and the VHL ligand moiety ( 42 ), respectively). Although five-term moieties are commonly considered not prone to be metabolized by h AOX unless it is fused with a phenyl ring to give a benzothiazole, one exception has been reported by Arora et al, showing that 2H-oxazoles substituted at the C-4 or C-5 position with variably decorated phenyl rings can undergo oxidation by mouse cytosolic AOX to give the corresponding 2-oxazolones. Therefore, we hypothesized that a similar oxidation pattern could occur in the selected PROTACs although this reaction has not been reported for substituted thiazoles to date.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the MS/MS fragment ion with m / z 218.0637 revealed that the soft spot for oxidation is located in the 4-methyl-5-phenyl-thiazole moiety that, in its unoxidized form, shows a fragment ion with m / z of 202.0685 (Supporting Information, Figure S2). Based on the findings by Arora et al., it is likely to assume that the metabolites formed for both 33 and 34 are the corresponding 2-thiazolones on the VHL moiety. This finding is noteworthy since VHL is one of the most common E3 ligases exploited for the PROTAC strategy and, therefore, additional larger-scale studies are currently in progress.…”
Section: Resultsmentioning
confidence: 99%
“…129 Interestingly, AO was recently found to oxidize 2H-oxazoles to 2-oxazolones under aerobic conditions. 109 Ziprasidone, a 5-hydroxytryptamine-2A and dopamine-2 receptors antagonist, showed reductive opening of the isothiazole ring in aerobic incubations with human liver cytosol (Figure 11B). 130 Isothiazole reduction was enhanced by inclusion of electron donor (2-hydroxypyrimidine) and inhibited by menadione, indicating aldehyde oxidase involvement, and the reaction also proceeded nonenzymatically in the presence of reduced glutathione.…”
Section: Journal Of Medicinalmentioning
confidence: 99%
“…Additionally, in nonfused aromatic systems, reducing ring size from 6 to 5 atoms has been reasonably successful, 95 with only oxazole reported as the low turnover substrate. 109 In addition to these, modulation of ring system electronics, either by rearranging heteroatoms and substituents, or introducing EDG or/and EWG, has generally resulted in mixed success rates.…”
Section: Drug Design Approaches To Modulatementioning
confidence: 99%
“…These heterocycles used as building blocks for various organic reactions, especially by cycloaddition reactions in the area of natural product synthesis. Specifically, multi‐substituted oxazolones such as 3 H ‐oxazol‐2‐ones and oxazolidin‐2‐ones displays superior pharmaceutical properties such as excellent cardiotonic activity, model compound for ring oxidation catalysed by aldehyde oxidase and cyclooxygenase‐2‐inhibitors . However, most of current synthetic procedures suffer from certain drawbacks such as toxic transition metal catalysts, corrosive reagents, multistep reaction and harsh reaction conditions .…”
Section: Introductionmentioning
confidence: 99%